Challenges in Implementing POSBINDU PTM with Limited Resources: an Evaluative Study - Armini, Ni Kadek; Sudirman, Sudirman; Parmi, Parmi; Eka Susianawati, Desak (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The increase in the prevalence of non-communicable diseases (NCDs) in Indonesia, including in Sigi District, Central Sulawesi Province, has prompted the need to strengthen early detection services through the POSBINDU NCD Program. Objective: To identify obstacles to the implementation of POSBINDU in the working area of the Kaleke Community Health Center. Method: Using a qualitative descriptive approach based on the framework of input, process, and output aspects. Data collection was conducted through in-depth interviews with four key informants involved in POSBINDU PTM. Result and Discussion: The results of the study indicate that the constraints include limited funding that is entirely dependent on Health Operational Assistance (BOK), low quality of human resources due to a lack of ongoing training, and facilities without adequate maintenance support. In addition, the implementation of POSBINDU activities has not been consistent with standard operating procedures and the simultaneous use of manual and digital recording systems. Furthermore, low participation among the productive age group is attributed to rigid schedules and non-strategic activity locations, compounded by equipment limitations that affect the completeness of services. Conclusions: This study concludes that POSBINDU PTM has limitations in terms of structural readiness, human resource quality, and adequate logistical support.